Effects of Periplaneta americana extracts on the growth and proliferation of cutaneous interstitial cells in cutaneous-wound healing - Liang, Zheng; Han, Guiqi; Luo, Zecheng; Li, Baojie; Liu, Wentao; Shen, Chongyang (Frontiers in Pharmacology, 2022)
Cutaneous-wound healing requires a coordinated reaction of multiple cells, including interstitial cells. Impaired recovery of cutaneous wounds can lead to various adverse health outcomes. Kangfuxin (KFX), an extract obtained from Periplaneta americana, is beneficial in cutaneous-wound healing. In this study, we isolated dermal cells from suckling mice and established a mouse model of cutaneous injury to evaluate the therapeutic effects of KFX. Cell biology experiments indicated that treatment with KFX improved cell proliferation and migration and also repaired cutaneous wounds in the animal model. Activation of the signal transducer and activator of transcription 3 (STAT3) signaling pathway was the core molecular mechanism of KFX. Our study provides a theoretical and practical basis for the clinical application of KFX in cutaneous-wound healing.